Peran Emotional Interference Terhadap Organization of Study Pada Mahasiswa: Peran Mediasi Prokrastinasi Akademik Dalam Model Self-Regulated Learning - Andria, Nadira Putri; Arlinkasari, Fitri (Jurnal Online Psikogenesis, 2024)
The COVID-19 pandemic has caused major changes in the education system with online learning as a solution. Good Self-Regulated Learning (SRL) is important in online learning. This study aims to determine the mediating role of academic procrastination on emotional interference in the organization of study among students who attend online lectures and determine the role of emotional interference in the organization of study. The research method used is quantitative non-experimental. The research subjects consisted of 153 active college students who had attended online lectures in the Greater Jakarta area. Measuring tools used include Difficulties in Engaging Goal-Directed Behavior (GOALS), Cognitive and Metacognitive Strategies: Organization and Academic Procrastination Scale (APS). The results showed that emotional interference has a direct negative and significant effect on the organization of study (β = -0.069, p=0.003). Emotional interference has a significant positive role in academic procrastination (β = 0.142, p<.001). The mediating variable, namelyacademic procrastination, has a significant negative effect on the organization of study (β = -0.275, p=.001). There is a significant negative indirect effect of emotional interference on organization of study with the path of emotional interference to academic procrastination and academic procrastination to organization of study (β = -0.039, p=0.003). There is a total pathway (β = -0.108, p<.001). The results of the study show that academic procrastination can play a role as a mediating variable, and emotional interference plays a negative and significant role in predicting organization of study.